2022
DOI: 10.1177/23197145221110281
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Savings Behaviour Among Rural Households: A Holistic Approach

Abstract: The main purpose of this research is to empirically examine the antecedents of household savings behaviour in the Metekele, Beneshangu Guzu state of Ethiopia. In this study, three broader factors (household characteristics, socio-economic variables and institutional variables) influencing savings decisions of households have been identified and examined. This study followed mixed method research design with questionnaire and in-depth interviews as the main instruments. Binary logistic regression has been mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 62 publications
(87 reference statements)
2
6
0
Order By: Relevance
“…It primarily happens because educational attainment and income level improve with increasing age and consequently the ability of the individual to save is also enhanced. The outcome of the study indicated that the likelihood of savings steps up with increasing age which is consistent with the findings of the studies carried out by Murendo and Mutsonziwa (2017), Bhat et al (2022) and Kibet et al (2009). However, the variable age did not emerge as a significant variable.…”
Section: Marriedsupporting
confidence: 89%
See 4 more Smart Citations
“…It primarily happens because educational attainment and income level improve with increasing age and consequently the ability of the individual to save is also enhanced. The outcome of the study indicated that the likelihood of savings steps up with increasing age which is consistent with the findings of the studies carried out by Murendo and Mutsonziwa (2017), Bhat et al (2022) and Kibet et al (2009). However, the variable age did not emerge as a significant variable.…”
Section: Marriedsupporting
confidence: 89%
“…It can be noticed that the savings behaviour of the farmers varies at each level of educational attainments. Empirical evidence suggests that farmers who have completed formal education are more likely to save regularly as compared to farmers who have no formal education (Bhat et al. , 2022).…”
Section: Fl Fc and The Savings Behaviour Among The Indian Farmersmentioning
confidence: 99%
See 3 more Smart Citations